Disorders of identity and sexual behavior: an epidemiological approach - Ieda Aparecida Diniz; Alex Rogério Chagas; Milla Wildemberg Fiedler; Rodrigo Buonincontro Ribeiro; Ana Laura Rocha e Silva; Richardson Miranda Machado (Universidade Federal do Ceará, 2013)
The research aimed to characterize patients affected by Identity Disorders and Sexual Behavior and identify their occurrence by sex, as well as the patient's origin, diagnosis and length of stay, type of admission and discharge and funding source for services rendered. This is a retrospective study conducted in a psychiatric clinic in the Midwest Miner. The sample consisted of 2715 patients, predominantly male (1518- 55.9%), age range 21-30 years (917- 33.7%), the origin of hospitalization for Psychosocial Care Centers (1123 - 41.3%), the diagnosis of "Other Disorders of sexual preference" (2567- 94.5%), the residence time of 1 to 30 days (1770-65.2%), the high medical (1818-66,9%), the first admissions (1775-65.3%) and Health System as the main funder (2004 to 73.1%). It was evident that the disorders are more common in young men and it was realized how little knowledge of health professionals about these disorders.